Fractionated plasma N‐glycan profiling of novel cohort of ATP6AP1‐CDG subjects identifies phenotypic association. Issue 2 (29th January 2023) - Alharbi, Hana; Daniel, Earnest James Paul; Thies, Jenny; Chang, Irene; Goldner, Dana L.; Ng, Bobby G.; Witters, Peter; Aqul, Amal; Velez‐Bartolomei, Frances; Enns, Gregory M.; Hsu, Evelyn; Kichula, Elizabeth; et al.
Abstract: ATP6AP1‐CDG is an X‐linked disorder typically characterized by hepatopathy, immunodeficiency, and an abnormal type II transferrin glycosylation pattern. Here, we present 11 new patients and clinical updates with biochemical characterization on one previously reported patient. We also document intrafamilial phenotypic variability and atypical presentations, expanding the symptomatology of ATP6AP1‐CDG to include dystonia, hepatocellular carcinoma, and lysosomal abnormalities on hepatic histology. Three of our subjects received successful liver transplantation. We performed N‐glycan profiling of total and fractionated plasma proteins for six patients and show associations with varying phenotypes, demonstrating potential diagnostic and prognostic value of fractionated N‐glycan profiles. The aberrant N‐linked glycosylation in purified transferrin and remaining plasma glycoprotein fractions normalized in one patient post hepatic transplant, while the increases of Man4GlcNAc2 and Man5GlcNAc2 in purified immunoglobulins persisted. Interestingly, in the single patient with isolated immune deficiency phenotype, elevated high‐mannose glycans were detected on purified immunoglobulins without glycosylation abnormalities on transferrin or the remaining plasma glycoprotein fractions. Given the diverse and often tissue specific clinical presentations and the need of clinical management post hepatic transplant in ATP6AP1‐CDG patients, these results demonstrate that fractionated plasma N‐glycan profiling could be a valuable tool in diagnosis and disease monitoring.